Pengaruh Kenaikan Pajak Pertambahan Nilai (PPN) 11% Terhadap Daya Beli Mobil Pada Auto2000 Pasteur Bandung - Marismiati, Marismiati; Woman, Silki Yulianti (Universitas Logistik dan Bisnis Internasional, 2024)
Tax regulations in Indonesia will experience many changes over time and changing times. Starting April 1, 2022, Indonesia has set the Value Added Tax (VAT) rate, which was previously 10%, to increase to 11%. One example of the the transaction that falls under Value Added Tax (VAT) is the sale of automobiles. This final project report aims to find out how the increase in VAT affects the purchasing power of cars at Auto2000 Bandung Pasteur. The employed research approach is quantitative, utilizing primary data collection which was obtained by distributing questionnaires to 91 consumers who bought cars at Auto2000 Pasteur Bandung in the period April 1 2022 – April 30 2023, and processed using the SPSS application with the Validation Assessment, Reliability Assessment, Normality Assessment, Spearman Rank Correlation Assessment, Simple Linear Regression Analysis, Coefficient of Determination Assessment, and Hypothesis Testing (t-test) were conducted. The findings indicated that 11% VAT increase had no effect on car purchasing power at Auto2000 Pasteur Bandung with a percentage of 0.5%.